HUBUNGAN PEMAKAIAN ALAT KONTRASEPSI SUNTIK DENGAN GANGGUAN MENSTRUASI PADA AKSEPTOR KB DIWILAYAH KERJA PUSKESMAS BASUKI RAHMAT KOTA BENGKULU - yulita elvira silviani (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2020)
The purpose of this study was to determine the relationship between the use of injectable contraceptives and menstrual disorders in family planning acceptors in the Basuki Rahmat Health Center Work Area in Bengkulu City. The design used in observational analytic research with Cross Sectional approach. The population in this study were 1-month active injection contraceptive participants and 3-month injection contraception in the 2018 Basuki Rahmat Health Center Work Area, totaling 1334 people. The sample in this study amounted to 93 respondents taken using purposive sampling technique. Data collection is done using primary and secondary data. Primary data in this study used a questionnaire consisting of respondent's identity, contraceptive use and menstrual disorders. Secondary data in this study came from the KB register in the Puskesmas Basuki Rahmat. The results showed that those using 3-month injection contraception were 55 respondents (59.1%) and 1-month injection contraception were 38 respondents (40.9%). Respondents who experienced menstrual disorders were 53 respondents (57%) and those who did not experience menstrual disorders were 40 respondents (43%). There is a significant relationship between the use of injectable contraceptives and menstrual disorders in family planning acceptors in the Basuki Rahmat Health Center Work Area of Bengkulu City